AB0205 Evidence for Endothelial-Mesenchymal Transition (Endomt) in Systemic Sclerosis Dermal Microvascular Endothelial Cells. (9th June 2015) - Manetti, M.; Romano, E.; Rosa, I.; Guiducci, S.; Bellando-Randone, S.; Ibba-Manneschi, L.; Matucci-Cerinic, M.
Abstract : Background: The accumulation of myofibroblasts is responsible for uncontrolled production of extracellular matrix during pathological fibrosis. Myofibroblasts may arise from different sources, such as expansion and activation of resident tissue fibroblasts, transition of epithelial cells into mesenchymal cells, and recruitment of bone marrow-derived circulating fibrocytes. Even endothelial cells (ECs) have an ability to acquire myofibroblastic features, providing proof of principle for the process of EndoMT [1]. EndoMT is a transdifferentiation by which ECs disaggregate, lose polarity, and undergo a change in their typical shape, becoming elongated and acquiring the ability to migrate into the surrounding tissue. It is a phenotypic conversion in which ECs lose their specific markers such as CD31, von Willebrand factor and VE-cadherin, and acquire mesenchymal cell products such as alpha-smooth muscle actin (alpha-SMA), S100A4/fibroblast-specific protein 1 (FSP1) and type I collagen [1]. Previous studies have shown that EndoMT can be induced in vitro by transforming growth factor-beta and may have a role in experimental dermal fibrosis [1, 2]. However, whether EndoMT may be involved in the pathogenesis of systemic sclerosis (SSc) remains to be determined. Objectives: To investigate whether SSc dermal microvascular endothelial cells (dMVECs) might represent a source of myofibroblasts via EndoMT. Methods: dMVECs were isolated from biopsies of the involved forearm skin from 6 patients with diffuse cutaneous SSc and from 6 healthy (H) subjects. CD31-positive cells were subjected to immunomagnetic isolation. The expression of CD31, VE-cadherin, alpha-SMA, S100A4/FSP1, CD90/Thy-1, type I collagen and Snail1 transcription factor was evaluated by immunofluorescence staining and Western blotting. Stress fibres were visualized with Alexa Fluor-488-conjugated phalloidin and cell nuclei were stained with DAPI. Results: On light microscopy, H-dMVECs exhibited a typical EC morphology with a large and flattened shape, whereas the majority of SSc-dMVECs had an elongated shape often characterized by many branches. Both H-dMVECs and SSc-dMVECs were homogeneously positive for the pan-EC marker CD31. However, the expression of both CD31 and VE-cadherin was significantly decreased in SSc-dMVECs compared with H-dMVECs (both p<0.001). Conversely, the expression of the mesenchymal cell marker CD90/Thy-1 was significantly increased in SSc-dMVECs (p<0.001 vs H-dMVECs). SSc-dMVECs co-expressed alpha-SMA, S100A4/FSP1 and type I collagen, which were instead undetectable in H-dMVECs. The formation of stress fibres was strongly increased in SSc-dMVECs (p<0.001 vs H-dMVECs). Strong expression and nuclear localization of Snail1 were constitutively found in SSc-dMVECs. Conclusions: Here, we provide the first evidence that SSc-dMVECs may undergo EndoMT resulting in an intermediate phenotype combining the expression of EC and myofibroblast markers and acquiring the capacity of type I collagen synthesis. In SSc, EndoMT might take center stage as a critical profibrotic switch and become a potential target for antifibrotic therapies. References: Manetti M, et al. Arthritis Rheum 2011;63:2164-7. Jimenez SA. ISRN Rheumatol 2013;2013:835948. Disclosure of Interest: None declared